Mechanical Properties of Fast-Growing Poplar Reinforced with Carbon Fiber - Ying Gao; Liwei Guo; Xiao Zhang; Yuzhuo Wang; Xiuying Yang; ChuanGuo Fu; Ziqing Liu (Advances in Civil Engineering)
This paper presents mechanical properties of fast-growing poplar specimens reinforced with carbon fibers. A total of 90 specimens including 10 contrast specimens were tested to investigate the influence from the following parameters: (a) different carbon fiber ratios (0.167%, 0.251%, 0.334%, 0.401%, and 0.501%) and (b) different fiber locations. The failure mode, compressive strength, elastic modulus, and axial deformation of specimens were analyzed. The test results indicate the following: (1) The compressive strength, elastic modulus, and axial deformation of specimens reinforced with carbon fiber were significantly improved compared with that of fast-growing poplar specimens. The compressive strength, elastic modulus, and axial deformation increased by 54.1–76.03%, 11.58–22.89%, and 24.86–60.06%, respectively. (2) There was little effect on the compressive strength of the specimen with the increase of carbon fiber ratio. With the increase of carbon fiber ratio, the elastic modulus of specimens slightly decreased and the axial deformation increased. The elastic modulus decreased by 1.39–18.69%, and the axial deformation increased by 10%–48%. (3) The different locations of the carbon fiber distribution resulted in a large difference in the compressive strength of the specimens, while the effects on the modulus of elasticity and axial deformation were not significant. Finally, the compressive strength calculation formula was proposed.